The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/md.0000000000007373
|View full text |Cite
|
Sign up to set email alerts
|

A multidisciplinary team approach for nutritional interventions conducted by specialist nurses in patients with advanced colorectal cancer undergoing chemotherapy

Abstract: Background & aims:Nutritional interventions for malnutrition in cancer patients can be helpful. However, concise intervention recommendations remain controversial. Thus, the aim of this study was to report on a nutrition intervention conducted by a multidisciplinary team of specialist nurses and to explore the effect of nutritional intervention on cancer patients.Methods:This prospective clinical trial study enrolled 110 colorectal cancer patients undergoing chemotherapy. The patients were evaluated upon admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…One psychosocial, two nutritional, and one physical activity interventions were included for review. [ 28 29 30 31 ] The comparability of study outcomes was limited because the study populations (cancer type or stage), objectives, and outcome measures were inconsistent among these studies.…”
Section: Resultsmentioning
confidence: 99%
“…One psychosocial, two nutritional, and one physical activity interventions were included for review. [ 28 29 30 31 ] The comparability of study outcomes was limited because the study populations (cancer type or stage), objectives, and outcome measures were inconsistent among these studies.…”
Section: Resultsmentioning
confidence: 99%
“…The RCT from Ravasco et al (2012) also showed that intensive nutritional counseling of colorectal cancer patients is the most effective means of improving nutritional status during radiotherapy. Lin et al (2017) and Dobrila-Dintinjana et al (2013) also demonstrated that individual nutritional counseling and administration of dietary supplements reduced weight loss and improved appetite in colorectal cancer patients, thus stabilizing nutritional status and reducing chemotherapyinduced morbidity. In the current study, the intensity of nutritional counseling depended on the frequency of GI side effects, which were most frequent in the intervention group with the use of inand outpatient counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the large catchment area of the hospital, consultations were occasionally carried out by telephone. The following areas were addressed: the selection of suitable foods and drinks with concrete portion sizes; methods of food preparation; distribution of total quantities over smaller more frequent meals; enrichment of meals with sources of energy and protein; and oral nutritional supplementation (Lin et al 2017 ). Between counseling sessions, patients kept a food and bowel diary, which was used to adapt the specific nutritional recommendations after each session depending on side effects and body weight (Arends et al 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Only few studies have explored the effect of nurse-led nutritional interventions among this patient group, yet the results have been promising. A multidisciplinary team approach for nutritional interventions (individual recipes, nutritional risk screening, total energy requirement calculation, education and diet adjustments) conducted by specialist nurses has obtained a positive effect on pre-albumin levels among CRC patients undergoing chemotherapy [21]. An individualised educational program with face-to-face and telephone counselling gained positive results on energy and total protein intake among patients with CRC (n = 19 + 21) in palliative care context [22].…”
Section: Introductionmentioning
confidence: 99%